Praktik Iddah dan Ihdad Serta Pemenuhan Hak-Hak Perempuan Dalam Perspektif Maslahat al-Tufi: Studi kasus di Desa Soki - St Maryam; Putri Rahyu; Suci Mulyati; Nuryadin; Salmiati (Maqasid: Jurnal Studi Hukum Islam, 2025)
This study examines the practices of ‘iddah and iḥdād as well as the fulfillment of women's rights after divorce through the lens of maṣlaḥat al-Ṭūfī. The research is motivated by a phenomenon in Soki Village, Belo Subdistrict, Bima Regency, where many women perceive ‘iddah merely as a prohibition against remarriage, without understanding the broader Islamic legal provisions governing it; some are entirely unfamiliar with the concepts of ‘iddah and iḥdād. Contributing factors include low levels of education, economic hardship, limited religious knowledge, and social influences. This research is a field study using an empirical or case study approach. Primary data were collected through interviews with local women and religious figures, while secondary sources include the Qur’an, Hadith, the Compilation of Islamic Law (KHI), Law No. 1 of 1974 on Marriage, academic journals, and al-Ṭūfī’s writings on the concept of maṣlaḥat. The findings reveal that the local practice of ‘iddah and iḥdād deviates from Islamic legal norms due to those influencing factors. Women who remarry during the ‘iddah period are considered to have committed acts categorized as mafsadat, which are legally impermissible. However, in cases where such actions stem from ignorance or emergency conditions such as financial pressure or the responsibility to support children these may be understood as forms of maṣlaḥat ḍarūriyyah, aimed at preserving life (ḥifẓ al-nafs), one of the primary objectives of Islamic law (maqāṣid al-sharī‘ah).